6 - Using Transnational Soap Operas to Redefine Beauty in Cameroon - Gwanvalla Ngehndab, Delphine (Africa Development, 2018)
This article elaborates on the different ways in which some market women in Bamenda, Cameroon, use transnational soap operas to redefine their understanding of beauty. The liberalisation of the audio-visual sector in Cameroon engineered a rise in television stations and an increase in the importation of soap operas causing television stations to constantly search the African-based rental agencies for quality programmes. To increase viewership, imported soap operas from the rest of the world like the Philippines, Brazil, India, China, and Thailand are broadcast on both private and national televisions capturing the attention of mainly women who watch these soap operas at home and at their market sheds. Some women love soap operas and the characters within so much so that their consumption is not without consequence on their daily appearances. From the application of lipstick, foundation, facial powder, nail vanish, dress and hair styles, and skin bleaching, foreign soap operas construct the cultural identities of local women who emulate the appearances of their preferred characters with the justification that appearances in soap operas are modern and contemporary. This article argues that the frequent broadcast of foreign soap operas pressures some local women to remake their bodies in attempts to resemble many of the female protagonists. A multimethod of data collection was utilised to collect data on the various meanings some selected market women in Bamenda make from their consumption of foreign soap operas. Both political economy and cultural studies are employed to capture the cultural exchange between the local and the global.